SELF-MANAGEMENT AND TEAM BUILDING AS KEYS TO SUCCESSFUL ENTERPRISE MANAGEMENT - Yakovlieva-Melnyk, N. H. (Systems and Technologies, 2025)
The article is dedicated to the issues of managing the human resource potential of enterprises modern conditions. The author explores key aspects of management practices that are necessary for achieving excellence in the contemporary business environment. The article reveals the concept of self-effectiveness as an important component of productivity linked to employees’ ability to manage their tasks, time and emotional state, which, in turn, has a positively impacts the overall performance of the enterprise.It is determined that, from the organization’s perspective, the ability of team members to self-manage is crucial for the effective functioning of the organization. An environment where much of the staff is unable to complete tasks, adhere to schedules, and strive for self-realization significantly complicates the significantly complicates the implementation of any projects. The article emphasizes current global trends in enterprise management, which increasingly focus on mandatory and regulated disclosures of ESG policies. With the Corporate Sustainability Reporting Directive (CSRD), the European Union establishes clear sustainability reporting standards and ESG data, and the implementation of ESG principles becomes an integral part of strategic investing, allowing not only for business development, but also for attracting investors who value responsible business practices.It has been clarified that the implementation of a corporate culture that fosters a sense of engagement and self-realization contributes to teamwork and the creation of a positive working environment. It is confirmed that when a company is socially responsible, it not only increases employee productivity, but also improves the company’s reputation in the market, particularly in terms of investment. Key principles include fairness, freedom, self-realization and development, support for diversity and innovation. Self-management and teamwork enable staff to take responsibility right where and when it is needed. Enterprises that have implemented the principles of self-organization and teamwork demonstrate significant success in adapting to changes and achieving strategic goals more rapidly. Overall, the article asserts that success in enterprise management lies in the formation of corporate policy through a combination of self-management, collaboration, and adaptability, which positively influence the achievement of corporate objectives in modern conditions.